Structural features and assessment of zymosan-induced arthritis in rat temporomandibular joint model using sulfated polysaccharide (Acta Scientiarum. Biological Sciences, 2014)
The green seaweed Caulerpa cupressoides var. lycopodium contains three SPs fractions (Cc-SP1, Cc-SP2 and Cc-SP3). Cc-SP1andCc-SP2 had anticoagulant (in vitro), pro- and antithrombotic, antinociceptive and/or anti-inflammatory (in vivo) effects. This study analyzed structural features and the antinociceptive and anti-inflammatory effects of Cc-SP1 on zymosan-induced acute arthritis of the rat temporomandibular joint (TMJ). Cc-SP1 was investigated by infrared technique. Male Wistar rats (200-240 g) received subcutaneously (s.c.) Cc-SP1 1h prior to intra-articular (i.art.) injection of zymosan (2 mg joint-1) or saline (0.9%) into the left TMJ. Mechanical hypernociception was measured by the electronic Von Frey method in the basal and 4h after zymosan injection. Animals were euthanized 6h after zymosan injection and the TMJ cavity was removed for total leukocyte counts from the synovial fluid and myeloperoxidase (MPO) activity assessment. Cc-SP1 (1, 3 or 9 mg kg-1) containing sulfate ester, galactose-6-sulfate, uronic acid and glycosidic linkages reduced zymosan-induced hypernociception (78.12, 81.13 and 87.43%, respectively, p < 0.01), and inhibited the total leukocyte influx (85, 88.14 and 89.95%, respectively, p < 0.01), being confirmed by MPO activity (p < 0.05). Therefore, Cc-SP1 reveals a pharmacological tool for treating inflammatory arthropathies.